Pembangunan sistem bantuan navigasi di pelabuhan menggunakan data ramalan pasang surut - Tengku Ali, Tengku Afrizal (2006)
Currently, maritime transportation has become one of the most important components in trade and industry of many countries. In any transportation, safety should be the main concern. As sea condition is dynamic, navigation becomes difficult without any equipment or guidance tools such as Global Positioning System (GPS) and Electronic Chart Display and Information System (ECDIS). ECDIS is rapidly gaining popular and has been accepted as a powerful tool to improve navigational safety. However, most of the ECDIS do not indicate the actual depth of water. The goal of this study is to develop a system that is able to update the water depth depending on tidal levels at given date and time, with various size of vessels draft. It can also determine locations of the sea that is safe for vessels to sail through. Although there are several factors that should be taken into account to ensure adequate under keel clearance, this study only take the draft of the vessel as a main factor. Other factors that may cause the changes in under keel clearance are excluded. This system was developed using Microsoft Visual Basic 6.0 and Esri MapObjects 2.3 to display the spatial data and Microsoft Access as tidal data prediction database. Mapping functions in GIS provides an excellent visualization tool and able to provide information in deciding the right passage for vessels safety. The system is able to produce a chart of the sea that has sufficient depth levels for vessels with different sizes to sail through. Safe depths are marked as blue points and unsafe depths are marked with red points. For navigation planning, calculation of the tide can be determine and this will produce a graph showing the times of sufficient tide in blue and times of insufficient tide in red. The benefit of this system would be an improvement in port safety since the actual depth of water and safe navigable area for vessels of different drafts are displayed on the system in real time